Design and Realization of an Auxiliary Teaching System for Chinese Painting Coursework - Wenjun Zhu (Forest Chemicals Review, 2022)
The traditional teaching method has low work efficiency and cannot meet the modern teaching tasks. The auxiliary teaching system that follows the trend has become the most concerned application in the field of education. At present, the auxiliary teaching system in the department where the author belongs is very scarce. Some of the existing systems have low technical content, single system functions, inconvenient operation and use, and do not support network applications. How to develop a set of auxiliary teaching system of traditional Chinese painting that suits the author's work needs, improve the work efficiency of teachers in the college, and facilitate students' independent learning is a major difficulty and challenge. The main task of this paper is to design and implement a comprehensive, flexible and efficient auxiliary teaching system for Chinese painting assignments according to the author's needs in the teaching of Chinese painting. The paper analyzes the development status of the auxiliary teaching system, and briefly introduces the main design content of this paper. Secondly, it introduces and analyzes the related technologies used in the development of the system, including J2EE architecture, Struts2 framework, Hibernate framework, Spring framework and Android SDK tools for developing mobile terminal applications. Thirdly, a detailed functional analysis and design of the system's overall architecture and business functions are carried out using software engineering related methodologies. Finally, the idea of the hierarchical design of the system is described in detail, and the detailed design and implementation of the four functional modules of the coursework management subsystem, the coursework situation completion subsystem, the educational affairs management subsystem and the system authority management subsystem are shown in detail. The system is thoroughly tested and aggregated for evaluation. The Chinese painting homework auxiliary teaching system designed and developed in this paper can well meet the application requirements of the author's teaching work. The system structure is simple, the implementation cost is low, and the functions are practical and comprehensive. use.